Islamization of Thomas Paine's Secular Thought - Hamid Fahmy Zarkasyi; Asrofil Fuad; Amir Reza Kusuma (al-Afkar, Journal For Islamic Studies, 2024)
Secularism is a problem that has become a disease among Muslims so it is dangerous if the secular concept develops. Thomas Paine is a secular figure who has a written work "The Age Of Reason" which is very influential for mankind. This article aims to correct Thomas Paine's secular thought based on Deism, so that this thought does not develop and has a negative impact on Muslims. In writing this article, the author uses qualitative methods by collecting primary and secondary data. The author uses the concept of Islamization of Sheikh Naquib Al Attas to rectify Thomas Paine's secular thinking by eliminating Thomas Paine's deism and incorporating elements of Islam based on the Qur'an and Hadith.